Factors Affecting Company Value - Khairul Rahman; Mohamad Fany Alfarisi; Masyhuri Hamidi (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the effect of managerial Ownership Structure, Liquidity, Profitability, Profit Growth and Capital Structure on firm value in manufacturing companies in the basic and chemical industrial sectors as well as in the consumer goods sector. The population of this study amounted to 142 companies listed on the IDX and used a sample of 20 companies in the basic and chemical industry sector and 16 companies in the consumer goods sector that have been listed on the IDX for the 2016-2020 period. Sampling in this study using non-probability sampling method using purposive sampling technique. The results of research in the basic and chemical industry sectors obtained that managerial ownership structure has an insignificant negative effect on firm value, Liquidity has a positive and insignificant effect on firm value and profitability, growth earnings and capital structure have a negative and significant effect on firm value in the basic and chemical industry sectors